Carotene Extraction from Crude Palm Oil Using Synthetic Absorbents - Abd. Latip, Razam (2000)
Crude, palm oil (CPO) has the highest content of carotenoids (500-700 ppm), a precursor of vitamin A. The only commercially viable method, so far, is transesterification followed by phase separation. However, the edible oil used as raw material has to be converted to methyl ester, therefore destroying the oil into non-edible product. The present study on carotene extraction from CPO focussed on adsorption using synthetic adsorbent followed by solvent extraction. By this method, the carotene can be recovered without destroying the oil therefore it can be used for food applications. The objectives of this study were mainly to find out the suitable adsorption process that selectively extracts the carotene from CPO and to determine the effect on CPO quality after going through this process. Based o n the studies conducted, it was found that the synthetic adsorbent SP850, SP825, HP20, Relite Exa 32 and Relite Exa 50 were capable of adsorbing carotene from CPO. The percentage of carotene extracted varied from 10 to 80% with the carotene concentration ranging from 1000 to 20,000 ppm depending on the process conditions. Combinations of adsorbent HP 20 and SP 850 slightly increased the percentage of carotene extracted. Adsorbent/CPO ratio of 4 was most suitable for this process for optimum recovery and concentration of carotene. The minimum adsorption time required was 0.5 hr. The IPA extraction time was determined based on the final carotene concentration required. The suitable temperature for adsorption and solvent extraction process was at 40°C. There is no significant different on the percentage of carotene extracted and carotene concentration between with and without agitation during IPA extraction process.The quality of CPO after going through the carotene extraction process slightly deteriorated in terms of moisture content, impurities, peroxide value (PV), anisidine value (AV). discriminant function (OF) and deterioration of bleachability index (DOBI). However changes in the chemical properties of the oil such as triglyceride (TG)carbon number and fatty acid composition (FAC) and it can be refined to produce refined bleached deodorized palm oil (RBDPO) that is able to meet Palm Oil Refinery Association of Malaysia (PORAM) standard specifications.